2009
DOI: 10.1089/aid.2008.0242
|View full text |Cite
|
Sign up to set email alerts
|

Liver Complications Have Reached a Plateau as Cause of Hospital Admission and Death in HIV Patients in Madrid

Abstract: Hospital admissions and deaths due to liver-related complications as result of chronic viral hepatitis are globally on the rise in HIV patients. However, a steady decline in liver-related hospitalizations and deaths has occurred at our HIV clinic in Madrid since year 2003. Hepatic complications are currently still responsible for 8.7% of all hospital admissions and one-third of in-hospital deaths, with hepatitis C virus infection by far the leading etiologic agent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 15 publications
1
6
0
Order By: Relevance
“…Other studies have demonstrated the increasing impact of chronic viral hepatitis and liver disease on hospital admission rates [22,25-27]. Prevention of hepatitis co-infection, timely treatment of chronic viral hepatitis in HIV co-infected patients, and careful monitoring of treatment related hepatotoxicity are important measures to reduce liver-related complications and subsequent hospitalizations.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have demonstrated the increasing impact of chronic viral hepatitis and liver disease on hospital admission rates [22,25-27]. Prevention of hepatitis co-infection, timely treatment of chronic viral hepatitis in HIV co-infected patients, and careful monitoring of treatment related hepatotoxicity are important measures to reduce liver-related complications and subsequent hospitalizations.…”
Section: Discussionmentioning
confidence: 99%
“…Our study suggests that liver disease, and perhaps cardiovascular diseases and cancers, are increasingly important reasons for hospitalization. Other studies have demonstrated the increasing impact of chronic viral hepatitis and liver disease on admission rates [2, 5, 2528], including one study that showed nearly 10% of admissions and one-third of in-hospital deaths were due to liver disease [29]. Many studies focused on the importance of hepatitis C virus on the increasing hospitalization rates of liver disease [2, 28]; of note, we found increasing rates of liver disease despite an overall low prevalence of hepatitis C among our cohort.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast with other cohorts, hepatitis C therapy had been given to a relatively high proportion (41%) of HIV/HCV coinfected patients in our cohort. In parallel with this wide use of hepatitis C therapy and associated benefit in terms of HCV clearance in a fraction of treated patients (42% in our cohort), we recently begun to appreciate that hospital admissions and deaths owing to HCV‐related liver disease have stabilized at our clinic [20]. The relatively large uptake of hepatitis C therapy in our cohort contrasts with rates below 10% in studies performed in North America [21,22], but it is in agreement with what is currently seen in other European countries [19,23,24].…”
Section: Discussionmentioning
confidence: 99%